Caliber of the common bile duct: effect of cholecystectomy and other factors in a ultrasonographic study of 8534 patients - Kratzer, W.; Wahl, S.; Vonend, C.; Schmidt, S. A; Öztürk, S.; Hänle, M. M.; Mason, R. A; Seufferlein, T.; Gräter, T. (Zeitschrift für Gastroenterologie, 2015)
Objective: The objective of the present study was to analyze the effects of different factors impacting the caliber of the common bile duct (CBD) and a comparison of maximum extrahepatic bile duct caliber in patients with and without a history of cholecystectomy.Material and Methods: A retrospective data analysis was undertaken of 8534 patients (4480 females; 4054 males; average age: 59.2 ± 18.0 years) with sonographic documentation of bile duct caliber. Maximum intra- and extrahepatic bile duct diameters were studied. The normal maximum diameter of the extrahepatic bile duct was defined as 7 mm. In patients who had undergone prior cholecystectomy, a maximum bile duct diameter < 10 mm was considered normal.Results: The average maximum diameter of the CBD amounted to 5.3 ± 3.0 mm for the overall collective. In patients who had undergone prior cholecystectomy, maximum CBD diameters in the normal range (< 7 mm) were documented in 55 %, while larger diameters (> 7 mm) were observed in 45 %. In the collective of patients without prior cholecystectomy, CBD diameters in the normal range (< 7 mm) were found in 81 %, with larger diameters observed in only 18.4 % of patients. In both subgroups, there was a significant association between age and bile duct diameter (for those with prior cholecystectomy, p = 0.0003; without prior cholecystectomy, p < 0.0001). No statistically significant influence on CBD diameter was observed for either prior cholecystectomy (p = 0.2116) or time interval since cholecystectomy (p = 0.3537). Females, both with and without a history of prior cholecystectomy, showed a 1.4 – 1.5-fold higher risk of exhibiting a CBD diameter > 7 mm (for those with prior cholecystectomy, p = 0.0485; without prior cholecystectomy, p < 0.001).Conclusions: Our data show a positive correlation between age and CBD diameter. There was no statistically significant relationship between CBD diameter and prior cholecystectomy, postoperative interval and BMI.
Keywords: Ductus hepatocholedochus; Alter; Choleczystektomie; Ultraschall